Review of Fighting Feelings: Lessons in Gendered Racism and Queer Life by Gulzar R. Charania (University of British Columbia Press) - Hannah Renda (Lateral)
In Fighting Feelings: Lessons in Gendered Racism and Queer Life, Gulzar R. Charania explores the gendered racialization of women of color through a plethora of interviews with her participants, paying specific attention to the intersection of identities that these women hold such as gender, race, sexuality, age, and socio-economic status. Charania centers the thoughts and experiences of racialized Black and women of color feminists to provide her readers with critical tools to navigate the lived experiences of racialized women while also acknowledging the violence of dominant narratives entrenched in white supremacy. By attending to the practices of scholars and theorists as well as the lives of her participants, Charania urges readers to reconsider the convergence of gender and sexuality in racialized hierarchies.